(untitled) (Research, Society and Development, 2022)
Objective: To survey the cases seen by the physiotherapy service and what procedures were used by these professionals and to trace the profile of patients admitted for cerebrovascular accident in the emergency unit in 2020. Methodology: Observational, retrospective study, cross-sectional, quantitative in nature, analyzing patients who were admitted to the emergency room of the Hospital Universitário do Oeste do Paraná (HUOP), in a period of one year. Data collection was performed using a previously elaborated form containing the study variables; an analysis was performed using simple descriptive statistics. Results: 1,020 records were found, where 17 were excluded. Of the frontal records, 186 were due to stroke, with a higher prevalence in ischemic stroke (77.42%), male gender (51.08%) and in those aged > 60 years (68.28%). There were 64 deaths, 48 ​​with ischemic stroke and 16 with hemorrhagic stroke. 84.95% of patients received physical therapy care. Conclusion: It is concluded that the current study is in line with other research, with a higher prevalence of ischemic stroke cases, in addition to higher rates of diagnoses in males and aged over 60 years. As for the outcome, most patients were discharged from the hospital, with only 64 deaths. Regarding physiotherapy, associated motor and respiratory behaviors were mainly used, and only 15.05% did not receive any type of physiotherapeutic care.